2022
DOI: 10.3390/ijerph19106092
|View full text |Cite
|
Sign up to set email alerts
|

Association of eHealth Literacy with Health Promotion Behaviors of Community-Dwelling Older People: The Chain Mediating Role of Self-Efficacy and Self-Care Ability

Abstract: In the digital age, electronic health literacy (eHealth literacy) of community-dwelling older people plays a potentially important role in their health behaviors which are critical for health outcomes. Researchers have documented that self-efficacy and self-care ability are related to this relationship. This study aimed to assess the relationship between eHealth literacy and health promotion behaviors among older people living in communities and explore the chain mediating role of self-efficacy and self-care a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 56 publications
1
10
0
Order By: Relevance
“…Our study found that age was correlated with EHL, as measured by both eHEALS and eHeLiOS-SB. This finding agrees with several previously published papers on the association between demographic variables such as age and eHealth literacy levels as measured by eHEALS, [26][27][28][29][30] such as one study of 262 20 to 65 year olds in Taiwan, which found that EHL levels were negatively associated with age. 26 Another study conducted in older adults by Wang et al similarly found that EHL levels as measured by eHEALS were lower on average in the older adult population than they were in university students.…”
Section: (72)supporting
confidence: 92%
See 1 more Smart Citation
“…Our study found that age was correlated with EHL, as measured by both eHEALS and eHeLiOS-SB. This finding agrees with several previously published papers on the association between demographic variables such as age and eHealth literacy levels as measured by eHEALS, [26][27][28][29][30] such as one study of 262 20 to 65 year olds in Taiwan, which found that EHL levels were negatively associated with age. 26 Another study conducted in older adults by Wang et al similarly found that EHL levels as measured by eHEALS were lower on average in the older adult population than they were in university students.…”
Section: (72)supporting
confidence: 92%
“…26 Another study conducted in older adults by Wang et al similarly found that EHL levels as measured by eHEALS were lower on average in the older adult population than they were in university students. 30 We believe that younger people have better EHL due to exposure to the internet and various types of online portals at a younger age in more recent generations. Cognitive decline in older populations may also be a factor, but we believe that increased exposure to the internet and technology among younger patients is likely the more significant contributor.…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies found that the self‐efficacy of both type II diabetes and haemodialysis patients was positively correlated with self‐care ability (Bağ & Mollaoğlu, 2010; Lee et al, 2016). A survey of 425 community elders from 3 communities in China showed that self‐efficacy and self‐care ability mediated a chain mediating effect, namely electronic health literacy → self‐efficacy → self‐care ability → health‐promoting behaviour (Wang, Song et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Digital technology has also been shown to help them lose weight and prevent chronic diseases such as hypertension and diabetes [19]. In terms of mental health, the elderly's use of digital technologies improves their self-efficacy [20], and the ability to connect with the outside world through digital media reduces loneliness [21]. However, they also face challenges with digital health services and some experience anxiety due to their inability to master the technologies [22].…”
Section: Literature Reviewmentioning
confidence: 99%